Implementation of Good Governance in Improving the Quality of Public Services at the Fatuaruin Village Office, Sasitamean District, Malaka District - LINO, Maria M; LAU, Yoanita Vianney; TODA, Hendrik (PT Keberlanjutan Strategis Indonesia, 2024)
This research aims to assess the Application of Good Governance in Enhancing Public Service Quality at the Fatuaruin Village Office, Sasitamean District, Malacca Regency, utilizing descriptive research methods with a qualitative approach. A total of 7 informants were purposively sampled for data collection through observations, interviews, and documentation analysis. The theoretical framework employed is based on the work of Ramdani et al (2022). The findings reveal challenges in the implementation of good governance at the Fatuaruin Village Office. Transparency is compromised, particularly in disseminating information related to business licensing services, leading to public perception that transparency efforts are not fully optimized. Responsiveness falls short as officials are frequently unavailable when needed, causing delays in service. The fairness of services provided is questioned, with instances of unequal treatment and illegal levies. Effectiveness and efficiency are criticized due to slow services that deviate from predetermined standards, resulting in community dissatisfaction with time and cost implications. Several obstacles impede the effective implementation of good governance in the village, including limited resources, insufficient awareness among officials, a lack of community involvement, and instances of corruption and nepotism. Recommendations include optimizing the principles of good governance—transparency, responsiveness, fairness, and efficiency—considering local contexts. This optimization is expected to enhance the quality of services provided, ensuring satisfaction within the community.